FEMINISM AS REFLECTED IN MARGOT LEE SHETTERLYâ€™S HIDDEN FIGURES NOVEL - Apriliantini A.M. Jaha; Sri Mulyani Darmastuti (JELLT (Journal of English Language and Language Teaching), 2018)
This research is a study of Margot Lee Shetterly's viewsof feminism. The objectives of the research are to find out and explain the kinds of gender discrimination experienced by women in the novel, and to identify and describe the ideas of feminism reflected in the novel. To find out and explain the problems presented in the novel,feminism theory is used to answer the objectives of this research.Qualitative research method is applied in this study. The data of this research was Â taken from a novel entitled Hidden Figures written by Margot Lee Shetterly in 2016. The data analysis was conducted by classifying and categorizing the data to find the inferences.the researcher also reads and re-read the novel carefully and then recorded the data into a systematic framework based on the theory.The result of this study shows some important points. First, there are five kinds of gender discrimination; marginality, subordination, stereotype, violance, and double burden. Second, the ideas of feminism is mostly reflected by three main characters of the novel, Dorothy Voughan; Marry Jackson; Katherine Johson.